2017
DOI: 10.1158/0008-5472.can-16-1589
|View full text |Cite
|
Sign up to set email alerts
|

RB Loss Promotes Prostate Cancer Metastasis

Abstract: RB loss occurs commonly in neoplasia but its contributions to advanced cancer have not been assessed directly. Here we show that RB loss in multiple murine models of cancer produces a prometastatic phenotype. Gene expression analyses showed that regulation of the cell motility receptor RHAMM by the RB/E2F pathway was critical for epithelial–mesenchymal transition, motility, and invasion by cancer cells. Genetic modulation or pharmacologic inhibition of RHAMM activity was sufficient and necessary for metastatic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 49 publications
4
63
0
1
Order By: Relevance
“…However, a significant increase (p=0.038) in copy number alterations in M1-poly versus M0-NM cases was observed in this small sample ( Figure 5D), consistent with heightened frequencies of amplifications and deletions associated with CIN in TCGA (Figure 2). Gain of MYC and loss of RB1 and SIAH3 were also identified, consistent with previous studies of genetic alterations associated with poor PC prognosis (Supplemental Figure 6A and B) [42][43][44]. Additional analysis of previously described CIN genes and drivers was also performed.…”
Section: Pnbx Analysis Revealed Heterogeneity Of Cin Insupporting
confidence: 86%
“…However, a significant increase (p=0.038) in copy number alterations in M1-poly versus M0-NM cases was observed in this small sample ( Figure 5D), consistent with heightened frequencies of amplifications and deletions associated with CIN in TCGA (Figure 2). Gain of MYC and loss of RB1 and SIAH3 were also identified, consistent with previous studies of genetic alterations associated with poor PC prognosis (Supplemental Figure 6A and B) [42][43][44]. Additional analysis of previously described CIN genes and drivers was also performed.…”
Section: Pnbx Analysis Revealed Heterogeneity Of Cin Insupporting
confidence: 86%
“…Few pathways were attenuated after RB depletion, despite the total number of genes altered in this category, underscoring the focused nature of E2F1 activity to elicit specific transcriptional programs. Pathways with attenuated enrichment include those that have been previously shown to interplay with the RB/E2F1 axis, such as epithelial-mesenchymal transition, hedgehog signaling, and myogenesis (Figure 6C, left; normalized enrichment score < -1.3) (59)(60)(61)(62)(63)(64). Conversely, a number of clinically relevant pathways were enriched upon RB loss, including canonical E2F targets, Myc targets, mitotic spindle, and DNA repair (Figure 6C, right; normalized enrichment score > 1.3).…”
Section: Delineation Of the Rb Loss-induced Transcriptomementioning
confidence: 99%
“…Previous studies showed that HMMR involved in oncogenic properties several mechanisms in multiple cancers, such as in uencing mitotic spindle assembly, regulating cell signaling pathways, and modulating the expression of growth factor receptor [29,33]. HMMR has also been found over expressed in gastric cancer 33 , glioblastoma 34 ,head and neck carcinomas 35 .The increased expression of HMMR directly leads to an increase in the metastatic potential of many types of tumors, including prostate cancer 36 , breast cancer 37 , colorectal cancer 38 ,and bladder cancer 39 . Available evidence showed that HMMR is considered to be an important downstream regulator of HA, which can lead to the rapid growth of bladder cancer cells 40 .One recent study showed that inhibition of HMMR expression in vitro can reduce the proliferation of bladder cancer cells and inhibit the growth of xenograft tumors in vivo 41 .These results suggest that HMMR mediates an important signaling pathway for bladder cancer cell growth and proliferation.…”
Section: Discussionmentioning
confidence: 99%